Pattern Formation in Morphogenesis: Problems and Mathematical Issues - Capasso, Vincenzo; Gromov, Mikhael; Harel-Bellan, Annick; Morozova, Nadya; Pritchard, Linda Louise (Springer proceedings in mathematics, 2013)
Preface -- Why Would a Mathematician Care About Embryology? M.Gromov.- PART I.BIOLOGICAL BACKGROUND -- Preface to the Biological Part -- Pattern Formation in Regenerating Tissues. A.Hoffmann and P.A. Tsonis -- Gradients and Regulatory Networks of Wnt Signalling in Hydra Pattern Formation. T.W. Holstein -- Modeling of Planar Cell Polarity Signaling. J.D. Axelrod -- Integrated Molecular Circuits for Stem Cell Activity in Arabidopsis Roots. B. Scheres -- The Mechanics of Tissue Morphogenesis. T. Lecuit -- Small Regulatory RNAs and Skeletal Muscle Cell Differentiation. A. Harel-Bellan, A.Polesskaya, I.Naguibneva, M.Ameyar-Zazoua, C.Degerny, J.Kropp, N.Nonne, M.Souidi, G.Kratassiouk, G.Pinna, L.L.Pritchard -- Pattern Formation in Sea Urchin Endomesoderm as Instructed by Gene Regulatory Network Topologies. I.S. Peter and E.H. Davidson -- PART II. MATHEMATICAL MODELS -- Modelling Oscillator Synchronisation During Vertebrate Axis Segmentation. P.J. Murray, P.K. Maini, and R.E. Baker -- Pattern Formation in Hybrid Models of Cell Populations. N. Bessonov, P. Kurbatova, V. Volpert.-An Integrative Approach to the Analysis of Pattern Formation in Butterfly Wings – Experiments and Models. T. Sekimura -- Modeling Morphogenesis in Multicellular Structures with Cell Complexes and L-systems. P. Prusinkiewicz and B. Lane -- Multistability and Hysteresis-based Mechanism of Pattern Formation in Biology. A. Marciniak-Czochra and A. Köthe -- How to knock out feedback Circuits in Gene Networks? H. Gruber, A. Richard, C. Soulé -- Formation of Evolutionary Patterns in Cancer Dynamics. M. Delitala and T. Lorenzi -- How Cell Decides Between Life and Death: Mathematical Modeling of Epigenetic Landscapes of Cellular Fates. A. Zinovyev, L. Calzone, S. Fourquet and E. Barillot -- PART III. IDEAS, HYPOTHESIS, SUGGESTIONS -- From Hydra to Vertebrates: Models for the Transition from Radial- to Bilateral-symmetric Body Plans, H. Meinhardt -- Cell Division and Hyperbolic Geometry. M. Gromov -- Formalistic Representation of the Cellular Architecture in the Course of Plant Tissue Development. I.V. Rudskiy -- The Geometry of Morphogenesis and the Morphogenetic Field Concept. N.Morozova and M.Shubin -- Randomness and Geometric Structures in Biology. V. Capasso.
Description based upon print version of record
Keywords: Aufsatzsammlung; Mathematisches Modell; Musterbildung; Morphogenese